EFFECT OF DIFFERENT PROTEIN LEVELS ON GROWTH PERFORMANCE, CARCASS TRAIT, DIGESTIBILITY AND SOME BLOOD BIEOCHEMICAL PARAMETERS IN AWASSI LAMBS - Yateem, CH. A. M.; Mustafa, K. N.; Alkass, J. E. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Twenty one Awassi lambs (4 month old and 23.59 ± 031 kg body weight) were used to investigate the effect of different levels of protein on growth, carcass traits, body composition, digestibility and some blood parameters. The lambs were divided equally and randomly and penned individually into three treatment groups, and fed ad lib on low protein (129.1 T1) medium protein (140.6 T2) and high protein (151.1 T3, g/kg DM). After 72 days of fattening, 5 lambs from each treatment were chosen randomly and slaughtered. The result showed that lambs fed on T3 diet had significantly (P